89.1k views
1 vote
Let f ( x ) = x 2 and g ( x ) = x + 6 , find: a . ( f ∘ g ) ( x ) = b . ( g ∘ f ) ( x ) = c . ( f ∘ g ) ( − 3 ) = d . ( g ∘ f ) ( − 3).

User Gizella
by
5.0k points

1 Answer

3 votes

Answer:


(fog)(x)=x^2+12x+36


(gof)(x)=x^2+6


(fog)(-3)=9


(gof)(-3)=15

Explanation:


f(x)=x^2


g(x)=x+6


(fog)(x)= f(g(x))

Plug in g(x)


(fog)(x)= f(g(x))=f(x+6)

replace x+6 for x in f(x)


(fog)(x)= f(g(x))=f(x+6)=(x+6)^2=x^2+12x+36


(fog)(x)=x^2+12x+36


(gof)(x)= g(f(x))


(gof)(x)= g(f(x))=g(x^2)=x^2+6


(gof)(x)=x^2+6


(fog)(-3)=(-3)^2+12(-3)+36=9


(gof)(-3)=(-3)^2+6=15

User Yeroc
by
5.3k points